Ortsnamen und Sprachengeschichte in Südtirol - Finsterwalder, Karl (ERDKUNDE, 1954)
I Sources of the history of language in South Tyrol. The claims of Battisti that, because a Latin tongue was spoken in some parts of South Tyrol, such as the Lower Vintschgau, Bozen, Deutschnofen and Welschnofen, as late as the 14th, 15th or even the 17th century, this is characteristic of the whole region, is diametrically opposed to the genuine, well-known facts as revealed by a great number of historical sources which, especially for the Bozen area, are available from the height of the Middle Ages onward. Research papers based on these sources were completely ignored by Battisti. II Battisti's place name studies as applied to the history of South Tyrol. Battisti's claim that all places in South Tyrol which have pre-German names date from the Roman occupation is a misrepresentation of facts. The truth, on the contrary, is that the majority of the settlements in South Tyrol, as indicated by their names, date from a period long before Romans or Latin people set foot in the Alps. With the methods applied by Battisti in his paper it could just as well be proved that the Rhineland too is Italian. Battisti claims that the historical development of the German-speaking population in the upper Etsch region was misunderstood by Dorrenhaus, and that the surnames of those South Tyrolese families which are derived from farms and fields prove that the majority of the population of South Tyrol consists of Germanised Ladins. This can, however, be refuted even by means of some of Battisti's own papers; in earlier, less propagandist^ publications, he had acknowledged several times the proved fact that the German language in South Tyrol owes its existence to the settling during the Middle Ages of the then uninhabited areas by German-speaking peasants. His present about turn can only have been dictated by political motives. III Battisti's maps of place names and his statistics of names. The substitution of a population history of South Tyrol by a kind of names statistics as applied by Battisti is a priori a naive thought. Simply to count on the basis of modern topographic maps, the German, Romance, and pre- Roman names of geographical features, and work out the respective proportions of the names as derived from each language, is an attempt using unsuitable data which does not even deserve the name statistics, since the names on these maps are an incomplete record, a mere selection only chosen for their intended use as staff or tourist maps, etc. The results of these statistics are then in addition crudely falsified, firstly he adds to the Romance names not only the pre-Roman names but also a number of purely German place names, be it in ignorance or to fit his argument; secondly, he further bases his proportions of names in German-speaking South Tyrol by including the names of adjoining undisputedly Latin provinces, the Trentino and Belluno, and thirdly, his worst offence, he does not take into account the changes of all pre-German place names in South Tyrol which, under the impact of the German language, occurred from the height or even the early Middle Ages onward, and which therefore represent an important historic source. Only by such violations of the genuine conditions does Battisti succeed in obtaining statistical results favouring the Latin element. In the same way as Battisti selected from the historic sources a few which seemed to favour his argument and presented them with much emphasis, while tacitly omitting the total result taking all the sources into consideration, he presents, as typical of South Tyrol, some sub-regions, for which he was worked out by his statistics - long ago refuted - favourable proportions of Romance names, but does not mention that wide areas of South Tyrol contain barely 3 per cent, place names of Latin origin. Battisti s maps as well as statistics and the book on the place names of South Tyrol are tendentious works, written without sufficient philologic knowledge of German; they may mislead an uninformed layman, but can never be a basis for a scholar's opinion. At any rate, Dorrenhaus' statements on the population history of South Tyrol are in no way refuted by them.